Virtual KLIA (Kuala Lumpur International Airport) / Yew Choo Hean - Yew, Choo Hean (2003)
Thesis is a subject that compulsory for all of the final year students of Computer Science or Information Technology in University of Malaya. It's divided into two phases and each phase is supposed to complete in each semester of final year. Thesis phase 1 (WXES 3181) is carried out in the first semester followed by thesis phase 2 (WXES 3182) in the second semester. To fulfill the requirement of my faculty, Virtual KLIA (Kuala Lumpur International Airport) has been chosen to become the title of my thesis. To success my thesis, I have apply all the knowledge and experience that I have gained throughout the 3 years in University of Malaya. Besides that, the knowledge and experience that I gained during the Industrial Training that I have gone through also helps me a lot in successing my thesis. I also have a chance to learn more skills of others authoring tools due to the requirements of my thesis. I believe that this will help me a lot in my future employment. Virtual KLIA is a web-based system that will focus more on one of the famous and important place in Malaysia, KLIA (Kuala Lumpur International Airport). Due to this reason, there would a lot people either our own local residents or foreigners like to know more information about it. This system allows users to get information about KLIA and feel the environment of the Departure Level in 3D environment. Besides that, map will be included in the system to let users know how to getting there. The system will also let users know about the facilities and services provided by KLIA.